17β-estradiol does not have a direct effect on the function of striatal cholinergic interneurons in adult mice in vitro - Kövesdi, Erzsébet; Udvarácz, Ildikó; Kecskés, Angéla; Szőcs, Szilárd; Farkas, Szidónia; Faludi, Péter; Jánosi, Tibor Z.; Ábrahám, István M.; Kovács, Gergely (Frontiers in Endocrinology, 2023)
The striatum is an essential component of the basal ganglia that is involved in motor control, action selection and motor learning. The pathophysiological changes of the striatum are present in several neurological and psychiatric disorder including Parkinson’s and Huntington’s diseases. The striatal cholinergic neurons are the main regulators of striatal microcircuitry. It has been demonstrated that estrogen exerts various effects on neuronal functions in dopaminergic and medium spiny neurons (MSN), however little is known about how the activity of cholinergic interneurons are influenced by estrogens. In this study we examined the acute effect of 17β-estradiol on the function of striatal cholinergic neurons in adult mice in vitro. We also tested the effect of estrus cycle and sexes on the spontaneous activity of cholinergic interneurons in the striatum. Our RNAscope experiments showed that ERα, ERβ, and GPER1 receptor mRNAs are expressed in some striatal cholinergic neurons at low level. In cell-attached patch clamp experiments, we could detect that high dose of 17β-estradiol affected spontaneous firing rate of these neurons in males. Our findings did not demonstrate any acute effect of low concentration of 17β-estradiol or show any association of estrus cycle or sexes with the activity of striatal cholinergic neurons. Despite estrogens did not induce changes in the intrinsic properties, they can still modulate synaptic inputs of cholinergic interneurons.